In vitro estimation of ruminal protein degradability of forages - Abdelgadir, I.E.O.; Cochran, R.C.; Vanzant, E.S.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ruminal degradation of alfalfa and prairie hay protein was estimated using a proteolytic enzyme from Streptomyces griseus with or without pretreatment with cellulase or a broad spectrum carbohydrase (driselase). Estimates of the undegradable intake protein (UIP) as a percentage of total protein derived from the protease alone were higher than that measured in the animal (i.e., in vivo). Pretreatment of hay samples with cellulase (48 h incubation) or driselase improved the accuracy of UIP predictions compared with those determined using the protease alone.
Keywords: Beef; Protein degradability; Cellulase; Driselase; Forage